Dwa rodzaje państwa w filozofii świętego Augustyna – wokół sensu kryterium różnicującego - Graban, Michał (Civitas. Studia z filozofii polityki, 2017)
The author discusses two cities as interpreted by St. Augustine, the Doctor of the Church. While the first one, which Augustine personally experienced on the example of the fall of the Roman Empire, is temporal, the second is located in the nether world. However, we can experience the blessings of the latter here and now provided that we live according to the word of God, i.e. in a Christian manner. The author uses the example of Rome and its earthly glories and refers to the history of the Hebrew kingdoms described in the Bible to outline various contexts of this dichotomy. He presents a critique of Roman polytheism, classified by Augustine as a false religion, and shows the profound political, social and historical significance of his teaching about the two cities. He concludes that St. Augustine’s teaching remains up-to-date in the present-day world.